2022
DOI: 10.21037/tp-22-60
|View full text |Cite
|
Sign up to set email alerts
|

Management of descending necrotizing mediastinitis with severe thoracic empyema using minimally invasive video-assisted thoracoscopic surgery: a case report

Abstract: Background: Descending necrotizing mediastinitis (DNM) is a rare but serious complication of odontogenic or pharyngeal infection spreading into the mediastinum. Very few childhood cases of DNM have been described. Case Description:We report a case of DNM complicated with severe thoracic empyema in a previously healthy 6-year-old girl who was successfully treated using minimally invasive video-assisted thoracoscopic surgery (VATS). The patient presented with odynophagia and dental pain, followed by rapid clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…DNM is a critical illness that requires appropriate treatment because pharyngeal and mediastinal abscesses can cause airway emergencies, as in our case 12. To successfully treat and recover from DNM, it is crucial to diagnose it quickly and employ a combination of broad-spectrum antibiotics, surgical drainage and intensive medical care 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNM is a critical illness that requires appropriate treatment because pharyngeal and mediastinal abscesses can cause airway emergencies, as in our case 12. To successfully treat and recover from DNM, it is crucial to diagnose it quickly and employ a combination of broad-spectrum antibiotics, surgical drainage and intensive medical care 6…”
Section: Discussionmentioning
confidence: 99%
“…It is usually treated by surgically draining of mediastinal collections 4. While there have been reports of DNM in adults, there have been very few cases reported in children 5 6. In this report, we describe a child with DNM caused by a retropharyngeal abscess.…”
Section: Introductionmentioning
confidence: 93%
“…We searched PubMed database for cases of S constellatus over the last decade and found that almost cases reported abscess formation ranging from the brain, orbit, lung, and mediastinum to the heart, ovaries, kidney, liver, spine, and thighs. [6][7][8][9][10][11] We complied 6 cases of DNM caused by S constellatus, and this was the second case of such severe, rapidly progressing septic shock (Table 1). [11][12][13][14][15][16] In another case, which was also very aggressive, a patient developed necrotizing fasciitis in the maxillofacial region, neck, and upper mediastinum after experiencing cold and fatigue, followed by rapid decompensation with resulting septic shock caused by S constellatus and Klebsiella oxytoca.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] We complied 6 cases of DNM caused by S constellatus, and this was the second case of such severe, rapidly progressing septic shock (Table 1). [11][12][13][14][15][16] In another case, which was also very aggressive, a patient developed necrotizing fasciitis in the maxillofacial region, neck, and upper mediastinum after experiencing cold and fatigue, followed by rapid decompensation with resulting septic shock caused by S constellatus and Klebsiella oxytoca. As we can see, the patients' age ranged from 6 to 77 years old and the length of stay varied from 14 to 42 days.…”
Section: Discussionmentioning
confidence: 99%
“…We have read with interest the study “ Management of descending necrotizing mediastinitis with severe thoracic empyema using minimally invasive video-assisted thoracoscopic surgery: a case report ”, in which Zhang et al presented a case of descending necrotizing mediastinitis (DNM) complicated with severe thoracic empyema in a young girl. This girl was very well treated using minimally invasive video-assisted thoracoscopic surgery (VATS) ( 1 ). We believe that this report is very intriguing and we consider VATS a relevant option in the therapeutic arsenal of the surgeons.…”
mentioning
confidence: 99%